PEMBERDAYAAN MASYARAKAT MELALUI PENDIDIKAN NONFORMAL BERKARAKTER CINTA TANAH AIR - Mahardhani, Ardhana Januar (JPK (Jurnal Pancasila dan Kewarganegaraan), 2018)
The main purpose of this paper is to provide input on community empowerment programs carried out through educational activities while promoting a sense of patriotism for the community. From the objectives to be achieved, it can be seen that the love of the homeland in society can be strengthened, one of which is through the implementation of learning. . The implementation of learning is carried out not only through formal education but also through non-formal education. This non-formal education is education that is not bound and organized based on the needs of the community. In many government agendas the development of human resources is always highlighted in order to develop an increasingly progressive and empowered society. The concept of empowerment carried out in this paper is not solely in improving the economic level, but the progress of thinking and acting on a problem is also evidence if the community is empowered. The conclusion that can be given in this paper is that non-formal education carried out by the community should continue to provide space for the community to develop themselves and still incorporate an element of character.